Analisis Perbedaan Individual dan Implikasi dalam Proses Pembelajaran - Firmansyah Firmansyah (Universitas Batanghari Jambi, 2021)
This study discusses several aspects of differences in general for each individual which includes, among others, differences in aspects: biological, psychological, intelligence, gender, ethnicity, and so on, as well as their implications in the learning process in the classroom. This research is library research, which aims to collect information related to individual differences and their implications in the learning process in the classroom. Research data collection was carried out using documentation techniques. The data analysis used inductive analysis. Based on the data analysis that has been done, it can be concluded that the individual characteristics of each lie in the biological (physiological) aspect, as well as the psychological aspect. These two aspects form a certain behavior in humans that makes them different from other humans. In addressing these differences, in the learning process in the classroom, teachers should be creative in managing the learning process in the classroom so that learning objectives can be achieved optimally.